LKB1 Regulates Vascular Macrophage Functions in Atherosclerosis - Wang, Xuewen; Liang, Ziwei; Xiang, Hong; Li, Yanqiu; Chen, Shuhua; Lu, Hongwei (Frontiers in Pharmacology, 2021)
Liver kinase B1 (LKB1) is known to shape the regulation of macrophage function by participating in multiple processes including cell metabolism, growth, and polarization. However, whether LKB1 also affects the functional plasticity of macrophages in atherosclerosis has not attracted much attention. Abnormal macrophage function is a pathophysiological hallmark of atherosclerosis, characterized by the formation of foam cells and the maintenance of vascular inflammation. Mounting evidence supports that LKB1 plays a vital role in the regulation of macrophage function in atherosclerosis, including affecting lipid metabolism reprogramming, inflammation, endoplasmic reticulum stress, and autophagy in macrophages. Thus, decreased expression of LKB1 in atherosclerosis aggravates vascular injury by inducing excessive lipid deposition in macrophages and the formation of foam cells. To systematically understand the role and potential mechanism of LKB1 in regulating macrophage functions in atherosclerosis, this review summarizes the relevant data in this regard, hoping to provide new ideas for the prevention and treatment of atherosclerosis.